2015
DOI: 10.1215/21562261-3089064
|View full text |Cite
|
Sign up to set email alerts
|

On some aspects of duality principle

Abstract: This paper is devoted to the study of the relation between Osserman algebraic curvature tensors and algebraic curvature tensors which satisfy the duality principle. We give a short overview of the duality principle in Osserman manifolds and extend this notion to null vectors. Here, it is proved that a Lorentzian totally Jacobi-dual curvature tensor is a real space form. Also, we find out that a Clifford curvature tensor is Jacobi-dual. We provide a few examples of Osserman manifolds which are totally Jacobidua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Recently, for algebraic curvature tensors in the Riemannian signature, it was shown that the duality principle is in fact equivalent to the Osserman property (in [5] for n ≤ 4, and in [14] for all n). In [4] this equivalence was extended to the Lorentzian signature, and it was also shown that the duality principle holds for algebraic curvature tensors R with the Clifford structure (all such R are Osserman). Further results on the duality principle can be found in [1,2].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, for algebraic curvature tensors in the Riemannian signature, it was shown that the duality principle is in fact equivalent to the Osserman property (in [5] for n ≤ 4, and in [14] for all n). In [4] this equivalence was extended to the Lorentzian signature, and it was also shown that the duality principle holds for algebraic curvature tensors R with the Clifford structure (all such R are Osserman). Further results on the duality principle can be found in [1,2].…”
Section: Introductionmentioning
confidence: 96%
“…The natural environment for using the duality principle for null vectors is Osserman manifolds of the neutral signature (p, p), by [8,Theorem 1.2]. In the signature (2, 2) there exists a manifold which is Osserman, but which does not satisfy the duality principle for null vectors, see [4,Section 6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any four-dimensional Osserman R is Jacobi-dual, see Andrejić [1]. Any Lorentzian totally Jacobidual R has constant sectional curvature, see Andrejić and Rakić [4]. Any fourdimensional Jacobi-dual R such that J X is diagonalizable for some nonnull X is Osserman, see Andrejić [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the Riemannian setting (g is positive definite), one of important features of an Osserman algebraic curvature tensor is the duality principle, given by Rakić [12]. Generalizations to a pseudo-Riemannian setting (see Andrejić and Rakić [3,4]) are possible by the following implication, Y is an eigenvector of J X =⇒ X is an eigenvector of J Y .…”
Section: Introductionmentioning
confidence: 99%